Locomotor and collision characteristics by phases of play during the 2017 rugby league World Cup. Issue 3 (2nd July 2020) - Rennie, Gordon; Dalton-Barron, Nicholas; McLaren, Shaun J.; Weaving, Dan; Hunwicks, Richard; Barnes, Chris; Emmonds, Stacey; Frost, Barry; Jones, Ben
ABSTRACT: Purpose: Understanding differences in locomotor and collision characteristics between phases of play can help rugby league coaches develop training prescription. There are no data currently available describing these differences at the elite international level. The aim of our study was to determine the differences in average speed (m∙min −1 ), high-speed running (>5.5 m∙s −1 ) per minute and collision frequencies per minute ( n ∙min −1 ) between attack and defence during the 2017 Rugby League World Cup (RLWC). Methods: Microtechnology data were collected from 24 male professional rugby league players from the same international squad across six matches of the RLWC. Data were then subject to exclusion criteria and stratified into forwards ( n = 9) and backs ( n = 7) before being analysed with linear mixed-effects models. Results: When comparing attack with defence, forwards and backs had substantially slower average speeds (effect size [ES]; ±90% confidence limits: −2.31; ±0.31 and −1.17; ±0.25) and substantially greater high-speed distance per minute (1.61; ±0.59 and 4.41; ±1.19). Forwards completed substantially more collisions per minute when defending (2.75; ±0.32) whilst backs completed substantially more when attacking (0.63; ±0.70). There was greater within- and between-player variability for collision frequency (coefficient of variation [CV] range; 25–28%) and high-speed distance (18–33%) per minute when compared to average speed (6–12%). Conclusions: There are distinct differences in locomotor and collision characteristics when attacking and defending during international rugby league match-play, yet the variability of high-speed running and collisions per minute is large. These data may be useful to plan or evaluate training practices.